(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A study has been undertaken to create a solid ground for the integrated control of the potato tuber moth Phthorimaea operculella Zeller in Tunisia. This paper presents the life table statistics, i.e. the generation time, the net reproductive rate, the intrinsic rate of increase and the finite rate of increase, at optimal conditions for development. Assuming that the population would increase exponentially with a stable age distribution the population would grow 0.169 fold per day per individual. The comparison of the life table statistics obtained for the Tunisian strain of the potato tuber moth with the same statistics of other strains showed that the Tunisian strain is not different from other strains. As a consequence, the wide range of data reported in the literature was used to calculate the stage-specific cohort parameters, i.e. developmental time and variability, stage-specific survival and age-specific fecundity. The stage-specific cohort parameters are calculated and expressed as functions of temperature.